Clinical and Radiographic Outcomes of Percutaneous Chevron-Akin Osteotomies for the Correction of Hallux Valgus Deformity. (January 2022) - Mikhail, Christopher M.; Markowitz, Jonathan; Di Lenarda, Luca; Guzman, Javier; Vulcano, Ettore
Background: Hallux valgus is a common cause of pain and dysfunction of the foot, sometimes requiring surgical correction when conservative measures fail. Although there are many methods of correction, one of the newer techniques is minimally invasive chevron-Akin (MICA). The aim of the current study is to evaluate clinical and radiographic effectiveness of MICA and narcotic use in a large patient cohort. Methods: All patients in this retrospective study were treated by a single fellowship-trained foot and ankle orthopaedic surgeon. Patient demographics were collected for all cases. Preoperative and postoperative intermetatarsal angle (IMA) and hallux valgus angle (HVA) were measured in all patients on weightbearing 3-views radiographs. The Foot Function Index (FFI) was obtained pre- and postoperatively at each visit. All patients were prescribed regular use of ibuprofen for 3 days with acetaminophen and oxycodone reserved for breakthrough pain. Use of narcotic pain medication was recorded. Results: A total of 274 feet in 248 patients were included in the study. Overall, 87.9% were female and 12.1% were male. The mean preoperative IMA and HVA were 13.4 and 29.1 degrees, respectively. The postoperative IMA and HVA were 4.9 and 8.9 degrees, respectively. The mean FFI score part A was 92 preoperatively and 43 postoperatively. Patient satisfaction was 91.6%. The mean postoperative 5 mg oxycodone pill consumption was 2.2. Conclusion: MICA is good method to correct hallux valgus deformity with low postoperative narcotic use. Level of Evidence: Level III, restrospective cohort study of a single surgeon practice.